Analisis Gap Kompetensi Digital SDM dan Dampaknya terhadap Transformasi Digital di Telkom Indonesia - Gerry Afriando Sipayung; Paskah Gloria S. Sipahutar; Siti Agriyani; Ananda Nazura; Nasrullah Hidayat (Publikasi Inspirasi Indonesia, 2026)
This study aims to analyze the digital competency gap among human resources (HR) and its impact on the digital transformation process at PT Telkom Indonesia (Persero) Tbk. The research employed a quantitative approach using Structural Equation Modeling (SEM) with SmartPLS, complemented by in-depth interviews with managers and digital transformation teams. The results reveal that Telkom Indonesia’s employees possess a moderately high level of digital competence (mean score = 3.65), yet a notable gap of 0.87 points exists compared to the ideal standard. The largest gaps occur in the digital content creation and digital problem-solving dimensions, which significantly and negatively affect the effectiveness of digital transformation (β = -0.642; p < 0.05). These findings indicate that the success of Telkom Indonesia’s digital transformation initiatives is highly dependent on the readiness of its human capital and the maturity of its digital culture. Therefore, enhancing digital competencies through targeted training, project-based learning, and mentoring programs is crucial to achieving sustainable organizational transformation.